KOMPARASI PENDAPATAN DAN PRODUKTIVITAS ANTARA PETANI JAHE PENERAP SOP (STANDARD OPERATING PROCEDURE) DAN NON SOP DI DESA GAYAMHARJO KECAMATAN PRAMBANAN KABUPATEN SLEMAN - Redono, Cucuk (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The study aims to determine the presence or no difference to the income and productivity between farmers ginger practitioners SOP (Standard Operating Procedure) and Non-SOP held in June 2015 in the village Gayamharjo Prambanan Sleman District of DIY. Data obtained from 30 respondents through interviews using a questionnaire. Farmers selected by proportional random sampling of 30 people are farmers who are members of 12 (twelve) farmer group. Data analysis was performed using t-test aimed to examine differences in the average of two samples on a variable. Results of the study that there is a difference between the income of farmers ginger practitioners SOP and Non-SOP, is influenced by the differences in selling prices and production. There is a difference to productivity between farmers ginger practitioners SOP and Non-SOP, the differences are influenced by cultivation techniques and the use of production factors.